Optical voltammetry of redox processes inside a nanohole with opto-iontronic microscopy - Zhu Zhang; Haolan Tao; Cheng Lian; René van Roij; Sanli Faez (Proceedings of the National Academy of Sciences, 2026)
Cyclic Voltammetry (CV) is the most commonly used method in electrochemistry to characterize electrochemical reactions, usually involving macroscopic electrodes. Here, we demonstrate an optical CV technique called opto-iontronic Microscopy, which is capable of monitoring electrochemical processes at the nanoscale. By integrating optical microscopy with nanohole electrodes, we enhance sensitivity in detecting redox reactions within volumes as small as an attoliter [ ( 100 nm ) 3 ]. This technique uses electric-double-layer modulation and lock-in detection to sensitively probe ion dynamics during cyclic voltammetry in nanoholes that are under total internal reflection illumination. We applied this method to study electric double layer (dis)charging coupled to ferrocenedimethanol [Fc(MeOH) 2 ] redox reactions. Experimental results were validated against a theoretical Poisson–Nernst–Planck–Butler–Volmer model, providing insights into ion concentration changes of reaction species that contribute to the optical contrast. This work opens up opportunities for high-sensitivity, label-free analysis of electrochemical reactions in nanoconfined environments, with potential applications in pure nanocrystal growth and monitoring.